INFLUENCE OF FIRM SIZE AND BOARD SIZE TOWARDS CAPITAL STRUCTURE DECISION (CASE STUDY: STATE-OWNED ENTERPRISE BANK IN INDONESIA) - Magdalena, Pangkey Hannah Maria; Pangemanan, Sifrid S; Tulung, Joy Elly (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The purpose of this research is to analyze the impact of Firm Size and Board Size toward Capital Structure simultaneously and partially. The objects of this research are state-owned enterprise banks that are listed in Indonesia Stock Exchange. This research is an associative study and used quantitative method which utilizes multiple regression analysis as the tool of analysis. Firm Size, Board Size and Capital Structure data of all banks were obtained for 10 years period each bank. The research results show that Firm Size did not give any significant impact toward Capital Structure partially, while Board Size, partially, gave significant impact toward Capital Structure. Simultaneously, Board Size and Firm Size give a significant impact toward Capital Structure. There are still a large part of what influences capital structure decision in Indonesian state-owned banks that should be examined, since these two variables examined in this research only provides 41.3% explanation. Keywords: capital structure, firm size, board size.